THE CRYO-EM STRUCTURE OF THE ∆RIMM IMMATURE 30S RIBOSOMAL SUBUNIT: A SNAPSHOT OF THE PROTEIN FACTORY UNDER CONSTRUCTION - Kent, Meredith C. (My University, 2012)
The ribosome is part of the indispensable machinery of every living cell. This large macromolecule, which decodes messenger RNA to produce proteins, is the subject of intense study as the mediator of an essential process. The prokaryotic ribosome is a major target for antimicrobial therapy, as its structure differs significantly from the eukaryotic ribosome. At present, the in vivo process of translation on the mature bacterial, or 70S, ribosome is well studied and increasingly understood, while the process of assembling the small (30S) and large (50S) subunits of this complex ribonucleoprotein enzyme has mostly been studied in vitro. Consequently, the significance of in vivo events such as ribosomal RNA (rRNA) maturation and factor-mediated maturation is incompletely understood. By studying the nature and structure of an in vivo assembled immature 30S subunit, this thesis aims to gain a better understanding of the key events in 30S subunit biogenesis. Deletion of the assembly cofactor Ribosome Maturation Factor M (RimM) results in slow growth, inefficient rRNA processing, and accumulation of nonfunctional, immature 30S subunits. This work presents the first cryo-EM model of the immature 30S purified from a RimM knockout strain of E. coli. The structure reveals distortion of the decoding centre and a disrupted 50S-binding interface, attesting to the importance of rRNA processing in 30S maturation. Additionally, the model suggests consequences for ribosomal protein incorporation and rRNA domain position relative to the mature 30S.
Keywords: 30S ribosome; ribosome assembly; RimM; assembly factor; cryo-EM; Biochemistry; Structural Biology; Biochemistry